H-reflex down-conditioning greatly increases the number of identifiable GABAergic interneurons in rat ventral horn. - Wang, Yu; Pillai, Shreejith; Jonathan Wolpaw; Xiang Yang Chen (Neuroscience letters, 2009)
H-reflex down-conditioning increases GABAergic terminals on spinal cord motoneurons. To explore the origins of these terminals, we studied the numbers and distributions of spinal cord GABAergic interneurons. The number of identifiable GABAergic interneurons in the ventral horn was 78% greater in rats in which down-conditioning was successful than in naive rats or rats in which down-conditioning failed. No increase occurred in other spinal lamina or on the contralateral side. This finding supports the hypothesis that the corticospinal tract influence that induces the motoneuron plasticity underlying down-conditioning reaches the motoneuron through GABAergic interneurons in the ventral horn.
Keywords: activity-dependent plasticity; GABAergic interneurons; H-reflex conditioning; learning and memory; Motor control; Spinal Cord

Effects of H-reflex up-conditioning on GABAergic terminals on rat soleus motoneurons. - Pillai, Shreejith; Wang, Yu; Jonathan Wolpaw; Xiang Yang Chen (The European journal of neuroscience, 2008)
To explore the role of spinal cord plasticity in motor learning, we evaluated the effects of H-reflex operant conditioning on GABAergic input to rat spinal motoneurons. Previous work indicated that down-conditioning of soleus H-reflex increases GABAergic input to soleus motoneurons. This study explored the effect of H-reflex up-conditioning on GABAergic input. Of nine rats exposed to H-reflex up-conditioning, up-conditioning was successful (H-reflex increase >or= 20%) in seven and failed (change < 20%) in two. These rats and eight naive control (i.e. unconditioned) rats were injected with cholera toxin subunit B-conjugated Alexa fluor 488 into the soleus muscle to retrogradely label soleus motoneurons. Sections containing soleus motoneurons were processed for GAD(67) [one of the two principal forms of the GABA-synthesizing enzyme glutamic acid decarboxylase (GAD)] with an ABC-peroxidase system. Two blinded independent raters counted and measured GABAergic terminals on these motoneurons. Unlike successful down-conditioning, which greatly increased the number of identifiable GABAergic terminals on the motoneurons, up-conditioning did not significantly change GABAergic terminal number. Successful up-conditioning did produce slight but statistically significant increases in GABAergic terminal diameter and soma coverage. These results are consistent with other data indicating that up- and down-conditioning are not mirror images of each other, but rather have different mechanisms. Although the marked changes in GABAergic terminals with down-conditioning probably contribute to H-reflex decrease, the modest changes in GABAergic terminals associated with up-conditioning may be compensatory or reactive plasticity, rather than the plasticity responsible for H-reflex increase. As a variety of spinal and supraspinal GABAergic neurons innervate motoneurons, the changes found with up-conditioning may be in terminals other than those affected in successful down-conditioning.
Keywords: activity-dependent plasticity; Learning; Memory; Motor control; Spinal Cord

Motor learning changes GABAergic terminals on spinal motoneurons in normal rats. - Wang, Yu; Pillai, Shreejith; Jonathan Wolpaw; Xiang Yang Chen (The European journal of neuroscience, 2006)
The role of spinal cord plasticity in motor learning is largely unknown. This study explored the effects of H-reflex operant conditioning, a simple model of motor learning, on GABAergic input to spinal motoneurons in rats. Soleus motoneurons were labeled by retrograde transport of a fluorescent tracer and GABAergic terminals on them were identified by glutamic acid decarboxylase (GAD)67 immunoreactivity. Three groups were studied: (i) rats in which down-conditioning had reduced the H-reflex (successful HRdown rats); (ii) rats in which down-conditioning had not reduced the H-reflex (unsuccessful HRdown rats) and (iii) unconditioned (naive) rats. The number, size and GAD density of GABAergic terminals, and their coverage of the motoneuron, were significantly greater in successful HRdown rats than in unsuccessful HRdown or naive rats. It is likely that these differences are due to modifications in terminals from spinal interneurons in lamina VI-VII and that the increased terminal number, size, GAD density and coverage in successful HRdown rats reflect and convey a corticospinal tract influence that changes motoneuron firing threshold and thereby decreases the H-reflex. GABAergic terminals in spinal cord change after spinal cord transection. The present results demonstrate that such spinal cord plasticity also occurs in intact rats in the course of motor learning and suggest that this plasticity contributes to skill acquisition.
Keywords: activity-dependent plasticity; GABA; H-Reflex; Memory; Motor control; Spinal Cord